Assessing development strategies and Africa’s food and nutrition security - Heidhues, Franz; Atsain, Achi; Nyangito, Hezron; Padilla, Martine; Ghersi, Gérard; Le Vallée, Jean-Charles (International Food Policy Research Institute, 2004)
On average, a typical developing country in Africa is assisted by about 30 aid institutions in the implementation of development strategies, yet Africa is still far from achieving food and nutrition security. Adequate access to food that is necessary for food security must be complemented with provision of health services, education, sanitary environments, and safe water sources, among other resources, to achieve nutrition security. -- from Text